Barriers to patient positioning for telephone cardiopulmonary resuscitation in out-of-hospital cardiac arrest. (June 2017) - Langlais, Blake T.; Panczyk, Micah; Sutter, John; Fukushima, Hidetada; Wu, Zhixin; Iwami, Taku; Spaite, Daniel; Bobrow, Bentley
Abstract: Background: 9-1-1 callers often face barriers preventing them from starting Telephone CPR (TCPR). The most common problem is getting patients to a hard, flat surface. This study describes barriers callers report when trying to move patients to a hard, flat surface and assesses conditions associated with overcoming these barriers. Methods: We audited 2396 out-of-hospital cardiac arrest (OHCA) audio recordings. A barrier was defined as any statement by the caller that the rescuer could not move the patient to the ground and into a supine position. Barriers were recorded and TCPR process metrics compared across the barrier and non-barrier groups. Results: There were 802 OHCAs in the study group. Roughly 26% had a barrier. Telecommunicators were less likely to start TCPR instructions in the barrier group than in the non-barrier group (OR: 0.63, 95% CI: 0.45-0.88; p = 0.007). Telecommunicator-directed bystander chest compressions were more than twice as likely to start in the non-barrier group (OR: 2.2, 95% CI: 1.6–3.2; p < 0.001). Median time to first compression was longer in the barrier group (276 s vs 171 s; p < 0.001). Rescuers were 3.7 times more likely to overcome a barrier and start compressions (OR: 3.7, 95% CI: 2.0–6.8; p < 0.001) when multiple bystanders were present. Conclusion: Inability to move patients to a hard, flat surface is associated with a reduced rate of TCPR and increased time to first compression. Assessing the conditions under which such barriers are overcome is important for telecommunicator training and can help improve rates and timeliness of TCPR.